Mirmecofauna em Eucalyptus grandis Hill ex Maiden sob diferentes sistemas de controle de plantas infestantes - Boscardin, Jardel (2012)
Plantings with forest species have economical, social and environmental importance for Brazil, contributing to decrease the suppression of native forests. Implantation is a decisive step towards the success of a forestry enterprise and, among the precautions to be taken at this stage, stands out the control of weeds. However, the removal of these plants can eliminate food sources and shelter for natural predators of pest insects, favoring the prevalence of some species over others and causing environmental and economical damages. Considering that ants are potential bioindicators of these changes, this study aimed to evaluate the ant fauna in an initial planting of Eucalyptus grandis Hill ex Maiden, under different systems of weeds control. To this end, in March 2011, was installed a planting of E. grandis, spaced 3m x 2m, together the State Foundation of Agricultural Research in Santa Maria, RS. The Experimental design was the Entirely Randomized, with six treatments, being each having an area half a hectare, comprising: total chemical control of weeds in the line and interline planting, with glyphosate (T1); total chemical control of weeds, in the line planting, with glyphosate (T2); chemical control of monocots in the line and interline planting, with sethoxydim (T3); chemical control of dicots in the line and interline planting, with bentazone (T4); total chemical control of weeds in the range of one meter parallel to the line planting, with glyphosate, and one meter in the central part of the leading, without control (T5), e witness, without weed control (T6). The herbicides application was sequential, in total area, before planting and after transplant in the planting line. The survey was conducted from March 2011 to February 2012, using attractive baits, soil trap and Berlese funnel. Each method contained six repetitions per treatment, at each sampling date. Were collected 46,675 ants, belonging to seven subfamilies and 37 species. There was not statistical difference (ANOVA, p> = 0.05) between the total of ant specimens collected in the areas assessed. The T2 treatment presented the greatest observed richness of species (Sobs = 35), and sampling efficiency of 99.0%. The genera Camponotus and Pheidole were the richest in species number, with six each. Camponotus punctulatus, commonly found in antropized areas, it was demonstrated very frequent (mf) in the area of T3 treatment, and uncommon (mp) in T6. There was significant difference (ANOVA, p < 0.05) between mean values of observed richness per sample, with the lowest value found in T1 treatment (Sobs = 0.4), in Berlese funnel. In terms of vegetation, was verified similarity among the areas least altered, and between the areas most simplified. Ectatomma permagnum e Gnamptogenys sulcata, potential predators of pest insects, demonstrated higher occurrence frequency, respectively, in the areas of treatments T6 (51.4%) and T2 (41.7%). We conclude that the indirect effects of the herbicides affect more the composition of ant species than the ant species richness.